2007
DOI: 10.1080/17429140701420003
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic bacteria mediate plant resistance against cotton bollworm

Abstract: The efficacy of endophytic bacterial strains was evaluated in cotton against American bollworm infestation under greenhouse conditions. Among the 103 endophytic bacterial strains, the Bacillus strains (EPCO 102 and EPCO 16) and Pseudomonas fluorescens strain Pf1 significantly reduced the bollworm incidence. Talc-based bioformulation of EPCO 102, EPCO 16 and P. fluorescens Pf1 with and without chitin in inducing systemic resistance was tested against bollworm. The application of the bioformulation through seed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The role of PPO in disease resistance is to oxidize phenolic compounds to quinines, which are often more toxic to microorganisms than the original phenols; the enzyme itself is inhibitory to viruses by inactivating the RNA of the virus (Vidhyasekaran 1988a, b). Recently, Rajendran et al (2007) demonstrated the endophytic behaviour of Bacillus and Pseudomonas strains that mediates the disease resistance in crop plants against plant pathogens. Similar to previous studies, P. fluorescens strain CHA0 alone and in combination with chitin-mediated induction of PPO in banana plantlets might account for the reduction of BBTD in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The role of PPO in disease resistance is to oxidize phenolic compounds to quinines, which are often more toxic to microorganisms than the original phenols; the enzyme itself is inhibitory to viruses by inactivating the RNA of the virus (Vidhyasekaran 1988a, b). Recently, Rajendran et al (2007) demonstrated the endophytic behaviour of Bacillus and Pseudomonas strains that mediates the disease resistance in crop plants against plant pathogens. Similar to previous studies, P. fluorescens strain CHA0 alone and in combination with chitin-mediated induction of PPO in banana plantlets might account for the reduction of BBTD in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Phytohormones like SA are able to regulate symbiosis and mediate ISR prompted by useful microbes in the interactions between plants and non-pathogenic rhizosphere microbes (De Vleesschauwer and Höfte, 2009; Zamioudis and Pieterse, 2012). Similarly, some PGPR-induced biochemical alterations prompt ISR in plants against herbivorous insects (Rajendran et al, 2007;van de Mortel et al, 2012;Wielkopolan and Obrepalska-Steplowska, 2016;Zebelo et al, 2016). Fahimi et al (2014) showed that the application of P. fluorescens strains UTPF68 and PF169 on cucumber led to a decrease in the average number of progeny produced by A. gossypii adults.…”
Section: Discussionmentioning
confidence: 99%
“…Limited information is available on such studies, especially in rice. The talc-based formulation containing beneficial microbes was found to be effective and cheaper for pests and diseases in different crops Rajendran et al 2007;Kavino et al 2007;Radjacommare et al 2002). Hence, the present study was carried out with the objectives of (i) isolation of effective Beauveria and in vitro bioassay against the rice leaffolder and (ii) Trying the talc-based powder formulation containing Beauveria strain and evaluating its efficacy against leaffolder under greenhouse conditions.…”
Section: Introductionmentioning
confidence: 99%